Anxiolytic activity of hydro-alcohol extract of Trema guineensis and its effect on behavioral activities of mice - Francois, Bakou Niangoran; Fidele, Kpahe Ziehi; Jules, Horo Yodanatchio; Eugene, Atayi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Objective was to study the anxiolytic activity of hydro ethanolic extract of Trema guineensis. Methods: Male swiss albino mice were used. Hydro ethanolic extract of Trema guineensis was administered in the doses of 5, 10 and 20 mg/kg IP hole board (HB), open field (OF), elevated plus maze (EPM) tests were used for determination of anxiolytic activity. Results: The hydro ethanolic extract of Trema guineensis significantly increased the number and duration of head poking in HB test. The extract also significantly increased the time spent and the number of entries in open arm in EPM. In OFT, the extract showed significant increase in number of rearing, assisted rearing and the squares crossed. Conclusions: In the present study, Trema guineensis exhibited anxiolytic activity which might be attributed to its phytoconstituents like alkaloid, steroid and triterpenes. Since Trema guineensis is ubiquitous and abundantly grown, it could be a fairly economical therapeutic agent for management of anxiety disorders.